2013
DOI: 10.1002/nvsm.1470
|View full text |Cite
|
Sign up to set email alerts
|

Social marketing on AIDS: using Transtheoretical model to understand current condom usage among commercial drivers in Accra, Ghana

Abstract: This is an exploratory research to utilise the Transtheoretical model to assess condom usage intentions among commercial drivers in Ghana. A convenience‐based non‐probability sampling method was employed, and a face‐to‐face questionnaire was administered on 132 commercial drivers in Accra. The analysis of variance and one sample t‐test statistical method was employed to establish relationship between variables based on the Transtheoretical model. The result reveals that over 71.9% of commercial drivers are at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Although scanty, it is fair to point out that few studies have been performed within the Ghanaian context. However, these studies have mainly focused on HIV/AIDS testing intentions among Ghanaian university students (Tweneboah‐Koduah and Owusu‐Frimpong, 2013), cervical cancer screening intentions among college students in Ghana (Abotchie and Shokar, 2009) and substance use and risky sexual behaviors among sexually experienced Ghanaian youth (Doku et al , 2012), to the neglect of issues concerning the adoption of technology (gym equipment use) in PA which this study seeks to address.…”
Section: Introductionmentioning
confidence: 99%
“…Although scanty, it is fair to point out that few studies have been performed within the Ghanaian context. However, these studies have mainly focused on HIV/AIDS testing intentions among Ghanaian university students (Tweneboah‐Koduah and Owusu‐Frimpong, 2013), cervical cancer screening intentions among college students in Ghana (Abotchie and Shokar, 2009) and substance use and risky sexual behaviors among sexually experienced Ghanaian youth (Doku et al , 2012), to the neglect of issues concerning the adoption of technology (gym equipment use) in PA which this study seeks to address.…”
Section: Introductionmentioning
confidence: 99%
“…SMIPs are more successful when they are grounded in the appropriate health behaviour change models (Andreasen, 1994;Fraze, Rivera-Trudeau, & McElroy, 2007). The extant literature indicated that in Ghana, the limited numbers of research carried out on social marketing (SM) have concentrated mostly on HIV/AIDS (Adu-Mireku, 2003;Tweneboah-Koduah & Owusu-Frimpong, 2013), contraceptives, and condom use (Addai, 1999;Tawiah, 1997), alcohol and drug use (Doku, Koivusilta, & Rimpelä, 2012), and malaria (Tweneboah-Koduah, Braimah, & Otuo, 2012 (BCI, 2015). These programmes were mainly to change the behaviour of Ghanaian women by creating awareness on breast cancer and encouraging women to undertake regular self and clinical examination as well as seek early treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers in the past have called for using a theoretical approach to design social marketing interventions, to enhance the effectiveness of the interventions and provide a theoretical framework for understanding a behavior (Tapp et al , 2013; Luca and Suggs, 2013; Ayikwa et al , 2020; Twum et al , 2021). Subsequently, Buchan et al (2012), Tweneboah-Koduah and Owusu-Frimpong (2013) argue that a single theoretical framework is not sufficient to understand and explain the complexities of behavior change. They further suggest that considering a large amount of unexplained variance by TPB, the researchers must include additional social marketing theories to increase the explanatory power of TPB (Buchan et al , 2012; Valizadeh et al , 2018).…”
Section: Discussionmentioning
confidence: 99%